THE STEPWISE EFFECT OF EMOTIONAL SELFEFFICACY PROCESSES AND EMOTIONAL EMPATHY ON YOUNG PEOPLE’S SATISFACTION WITH LIFE - Totan, Tarık; Şahin, Rukiye (European Scientific Journal, ESJ, 2015)
Considering that the development of the skills of empathy and a sense of self-efficacy have positive effects on satisfaction with life, the purpose of the research is to examine the effect of these source variables on satisfaction with life on an emotional basis. The 228 participants included 104 men (45.6%) and 124 (54.4%) women. The average age of the participants was 20 years and 5 months. The Emotional Self-efficacy Scale, the Emotional Empathy Scale, the Satisfaction with Life Scale and a personal information form were used as data collection tools. While it was determined that emotional self-efficacy and satisfaction with life in terms of emotional empathy have a positive correlation, it was also concluded from the stepwise regression analysis that, except for the variable of understanding feelings, all other variables of emotional self-efficacy and emotional empathy affect satisfaction with life.